Combination drug strategies for biofilm eradication using synthetic and natural agents in KAPE pathogens - Bari, Anurag Kumar; Belalekar, Tanvi Sandeep; Poojary, Aruna; Rohra, Seema (Frontiers in Cellular and Infection Microbiology, 2023)
Antibiotic resistance is a global threat caused by factors such as overuse of antibiotics, lack of awareness, development of biofilms etc. World Health Organization released a list of global priority pathogens which consisted of 12 species of bacteria categorized as expressing critical, high and medium resistance. Several Gram-negative and Gram-positive species are known to cause wide varieties of infections and have become multidrug or extremely drug resistant. Pathogens causing infections associated with invasive medical devices are biofilm producers and hence their treatment becomes difficult due to a structurally stable matrix which prevents antibiotics from penetrating the biofilm and thereby showing its effects. .. Factors contributing to tolerance are inhibition of penetration, restricted growth and activation of biofilm genes.. Combination drug therapies has also shown potential to eradicate biofilm infections.. A combination of inhaled Fosfomycin/tobramycin antibiotic strategy has been effective against Gram-negative as well as Gram positive organisms. Along with antibiotics, use of natural or synthetic adjuvants shows promising effects to treat biofilm infections. Fluroquinolone activity on biofilms is disrupted by low oxygen tension in the matrix, a strategy known as hyperbaric oxygen treatment that can enhance efficacy of antibiotics if well optimized. Adjuvants such as Ethylenediaminetetraacetic acid (EDTA), Sodium Dodecyl Sulphate (SDS) and chlorhexidine act by killing non-growing microbial cells aggregated on the inner layer of the biofilm. This review aims to list down current combination therapies used against Gram-negative and Gram-positive biofilm forming pathogens and brief about comparison of combination drugs and their efficacies.